2011
DOI: 10.1097/dcr.0b013e3182270af1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sacral Nerve Stimulation for the Treatment of Fecal Incontinence

Abstract: This study demonstrates that sacral nerve stimulation can be an effective treatment for patients with fecal incontinence; however, when analyzed by intention to treat, the symptoms of fecal incontinence continue in the majority (74%) of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 40 publications
1
29
1
Order By: Relevance
“…Of those that received permanent stimulation, 20 % failed to regain the benefit experienced during the evaluation phase. Of 37 patients who underwent placement of a permanent SNS, 14 had a 50 % reduction in incontinent episodes and 13 became continent [22]. These outcomes are not as favourable as those previously reported, in which PNE was successful in up to 90 and 80 % experienced a reduction in incontinent episodes [23].…”
Section: Sacral Nerve Stimulationmentioning
confidence: 52%
“…Of those that received permanent stimulation, 20 % failed to regain the benefit experienced during the evaluation phase. Of 37 patients who underwent placement of a permanent SNS, 14 had a 50 % reduction in incontinent episodes and 13 became continent [22]. These outcomes are not as favourable as those previously reported, in which PNE was successful in up to 90 and 80 % experienced a reduction in incontinent episodes [23].…”
Section: Sacral Nerve Stimulationmentioning
confidence: 52%
“…A low-amplitude electrical current is applied to a sacral nerve, usually S3, via an electrode in the sacral foramen. An advantage of SNS over alternative surgical techniques is the ability to evaluate patient response to SNS, via a temporary external neurostimulator, before permanent neurostimulator implantation 57. SNS must be performed in the operating room and requires general or local anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…Success rates, defined by the majority of studies as >50% reduction in symptoms, have ranged from 67 to 100% [85]. However, in a prospective 5-year study with strict definitions of success, Boyle et al reported that~74% of patients continued to have FI [85].…”
Section: Sacral Nerve Stimulationmentioning
confidence: 92%
“…However, in a prospective 5-year study with strict definitions of success, Boyle et al reported that~74% of patients continued to have FI [85]. A randomized controlled study by Tjandra et al randomized patients with FI into SNS or medical therapy group consisting of pelvic floor exercises, bulking agents and dietary manipulation.…”
Section: Sacral Nerve Stimulationmentioning
confidence: 94%